Episodic memory deficit in HIV infection: common phenotype with Parkinson’s disease, different neural substrates - Rosemary Fama; Eva M. Müller-Oehring; Taylor F. Levine; Edith V. Sullivan; Stephanie A. Sassoon; Priya Asok; Helen M. Brontë-Stewart; Kathleen L. Poston; Kilian M. Pohl; Adolf Pfefferbaum; Tilman Schulte (Brain Structure and Function, 2023)
Episodic memory deficits occur in people living with HIV (PLWH) and individuals with Parkinson’s disease (PD). Given known effects of HIV and PD on frontolimbic systems, episodic memory deficits are often attributed to executive dysfunction. Although executive dysfunction, evidenced as retrieval deficits, is relevant to mnemonic deficits, learning deficits may also contribute. Here, the California Verbal Learning Test-II, administered to 42 PLWH, 41 PD participants, and 37 controls, assessed learning and retrieval using measures of free recall, cued recall, and recognition. Executive function was assessed with a composite score comprising Stroop Color-Word Reading and Backward Digit Spans. Neurostructural correlates were examined with MRI of frontal (precentral, superior, orbital, middle, inferior, supplemental motor, medial) and limbic (hippocampus, thalamus) volumes. HIV and PD groups were impaired relative to controls on learning and free and cued recall trials but did not differ on recognition or retention of learned material. In no case did executive functioning solely account for the observed mnemonic deficits or brain-performance relations. Critically, the shared learning and retrieval deficits in HIV and PD were related to different substrates of frontolimbic mnemonic neurocircuitry. Specifically, diminished learning and poorer free and cued recall were related to smaller orbitofrontal volume in PLWH but not PD, whereas diminished learning in PD but not PLWH was related to smaller frontal superior volume. In PD, poorer recognition correlated with smaller thalamic volume and poorer retention to hippocampal volume. Although memory deficits were similar, the neural correlates in HIV and PD suggest different pathogenic mechanisms.

Aging Accelerates Postural Instability in HIV Infection: Contributing Sensory Biomarkers - Edith V. Sullivan; Natalie M. Zahr; Stephanie A. Sassoon; Adolf Pfefferbaum (Journal of Neuroimmune Pharmacology, 2022)

Altered Cerebro-Cerebellar Dynamic Functional Connectivity in Alcohol Use Disorder: a Resting-State fMRI Study - Majd Abdallah; Natalie M. Zahr; Manojkumar Saranathan; Nicolas Honnorat; Nicolas Farrugia; Adolf Pfefferbaum; Edith V. Sullivan; Sandra Chanraud (The Cerebellum, 2021)

Effects of age, sex, and puberty on neural efficiency of cognitive and motor control in adolescents - Tilman Schulte; Jui-Yang Hong; Edith V. Sullivan; Adolf Pfefferbaum; Fiona C. Baker; Weiwei Chu; Devin Prouty; Dongjin Kwon; Mary J. Meloy; Ty Brumback; Susan F. Tapert; Ian M. Colrain; et al. (Brain Imaging and Behavior, 2020)

Regional growth trajectories of cortical myelination in adolescents and young adults: longitudinal validation and functional correlates - Dongjin Kwon; Adolf Pfefferbaum; Edith V. Sullivan; Kilian M. Pohl (Brain Imaging and Behavior, 2020)

Dissociable Contributions of Precuneus and Cerebellum to Subjective and Objective Neuropathy in HIV - Natalie M. Zahr; Kilian M. Pohl; Adolf Pfefferbaum; Edith V. Sullivan (Journal of Neuroimmune Pharmacology, 2019)

Relations between cognitive and motor deficits and regional brain volumes in individuals with alcoholism - Rosemary Fama; Anne-Pascale Le Berre; Stephanie A. Sassoon; Natalie M. Zahr; Kilian M. Pohl; Adolf Pfefferbaum; Edith V. Sullivan (Brain Structure and Function, 2019)

The mediating role of cortical thickness and gray matter volume on sleep slow-wave activity during adolescence - Aimée Goldstone; Adrian R. Willoughby; Massimiliano de Zambotti; Peter L. Franzen; Dongjin Kwon; Kilian M. Pohl; Adolf Pfefferbaum; Edith V. Sullivan; Eva M. Müller-Oehring; Devin E. Prouty; Brant P. Hasler; Duncan B. Clark; et al. (Brain Structure and Function, 2018)

Structural brain anomalies in healthy adolescents in the NCANDA cohort: relation to neuropsychological test performance, sex, and ethnicity - Edith V. Sullivan; Barton Lane; Dongjin Kwon; M. J. Meloy; Susan F. Tapert; Sandra A. Brown; Ian M. Colrain; Fiona C. Baker; Michael D. De Bellis; Duncan B. Clark; Bonnie J. Nagel; Kilian M. Pohl; et al. (Brain Imaging and Behavior, 2017)

Concomitants of alcoholism: differential effects of thiamine deficiency, liver damage, and food deprivation on the rat brain in vivo - Natalie M. Zahr; Edith V. Sullivan; Torsten Rohlfing; Dirk Mayer; Amy M. Collins; Richard Luong; Adolf Pfefferbaum (Psychopharmacology, 2016)

Task-rest modulation of basal ganglia connectivity in mild to moderate Parkinson’s disease - Eva M. Müller-Oehring; Edith V. Sullivan; Adolf Pfefferbaum; Neng C. Huang; Kathleen L. Poston; Helen M. Bronte-Stewart; Tilman Schulte (Brain Imaging and Behavior, 2015)

Compromised frontocerebellar circuitry contributes to nonplanning impulsivity in recovering alcoholics - Young-Chul Jung; Tilman Schulte; Eva M. Müller-Oehring; Kee Namkoong; Adolf Pfefferbaum; Edith V. Sullivan (Psychopharmacology, 2014)

Thalamic volume deficit contributes to procedural and explicit memory impairment in HIV infection with primary alcoholism comorbidity - Rosemary Fama; Margaret J. Rosenbloom; Stephanie A. Sassoon; Torsten Rohlfing; Adolf Pfefferbaum; Edith V. Sullivan (Brain Imaging and Behavior, 2014)

Rat strain differences in brain structure and neurochemistry in response to binge alcohol - Natalie M Zahr; Dirk Mayer; Torsten Rohlfing; Oliver Hsu; Shara Vinco; Juan Orduna; Richard Luong; Richard L Bell; Edith V Sullivan; Adolf Pfefferbaum (Psychopharmacology, 2014)

Modulation of limbic-cerebellar functional connectivity enables alcoholics to recognize who is who - Anne-Lise Pitel; Sandra Chanraud; Eva M. Müller-Oehring; Adolf Pfefferbaum; Edith V. Sullivan (Brain Structure and Function, 2013)

Pontocerebellar contribution to postural instability and psychomotor slowing in HIV infection without dementia - Edith V. Sullivan; Margaret J. Rosenbloom; Torsten Rohlfing; Carol A. Kemper; Stanley Deresinski; Adolf Pfefferbaum (Brain Imaging and Behavior, 2011)

Frontally mediated inhibitory processing and white matter microstructure: age and alcoholism effects - Ian M. Colrain; Edith V. Sullivan; Judith M. Ford; Daniel H. Mathalon; Selwyn-Lloyd McPherson; Brian J. Roach; Kate E. Crowley; Adolf Pfefferbaum (Psychopharmacology, 2011)

Electrophysiological evidence of enhanced performance monitoring in recently abstinent alcoholic men - Mayra L. Padilla; Ian M. Colrain; Edith V. Sullivan; Benjamin Z. Mayer; Sharon R. Turlington; Lindsay R. Hoffman; Amanda E. Wagstaff; Adolf Pfefferbaum (Psychopharmacology, 2011)

MR Diffusion Tensor Imaging: A Window into White Matter Integrity of the Working Brain - Sandra Chanraud; Natalie Zahr; Edith V. Sullivan; Adolf Pfefferbaum (Neuropsychology Review, 2010)

Pontocerebellar volume deficits and ataxia in alcoholic men and women: no evidence for “telescoping” - Edith V. Sullivan; Torsten Rohlfing; Adolf Pfefferbaum (Psychopharmacology, 2010)

Contribution of Regional White Matter Integrity to Visuospatial Construction Accuracy, Organizational Strategy, and Memory for a Complex Figure in Abstinent Alcoholics - Margaret J. Rosenbloom; Stephanie A. Sassoon; Adolf Pfefferbaum; Edith V. Sullivan (Brain Imaging and Behavior, 2009)

Relevance of Iron Deposition in Deep Gray Matter Brain Structures to Cognitive and Motor Performance in Healthy Elderly Men and Women: Exploratory Findings - Edith V. Sullivan; Elfar Adalsteinsson; Torsten Rohlfing; Adolf Pfefferbaum (Brain Imaging and Behavior, 2009)

Frontal Callosal Fiber Integrity Selectively Predicts Coordinated Psychomotor Performance in Chronic Alcoholism - Margaret J. Rosenbloom; Stephanie A. Sassoon; Rosemary Fama; Edith V. Sullivan; Adolf Pfefferbaum (Brain Imaging and Behavior, 2008)

Callosal Compromise Differentially Affects Conflict Processing and Attentional Allocation in Alcoholism, HIV, and Their Comorbidity - Tilman Schulte; Eva M. Müller-Oehring; Harold Javitz; Adolf Pfefferbaum; Edith V. Sullivan (Brain Imaging and Behavior, 2008)

Neurocircuitry in alcoholism: a substrate of disruption and repair - Edith V. Sullivan; Adolf Pfefferbaum (Psychopharmacology, 2005)